A multi–step comparison of short–read full plastome sequence assembly methods in grasses. Issue 4 (5th August 2014) - Wysocki, William P.; Clark, Lynn G.; Kelchner, Scot A.; Burke, Sean V.; Pires, J. Chris; Edger, Patrick P.; Mayfield, Dustin R.; Triplett, Jimmy K.; Columbus, J. Travis; Ingram, Amanda L.; Duvall, Melvin R.
Abstract: Technological advances have allowed phylogenomic studies of plants, such as full chloroplast genome (plastome) analysis, to become increasingly popular and economically feasible. Although next–generation short–read sequencing allows for full plastomes to be sequenced relatively rapidly, it requires additional attention using software to assemble these reads into comprehensive sequences. Here we compare the use of three de novo assemblers combined with three contig assembly methods. Seven plastome sequences were analyzed. Three of these were Sanger–sequenced. The other four were assembled from short, single–end read files generated from next–generation libraries. These plastomes represented a total of six grass species (Poaceae), one of which was sequenced in duplicate by the two methods to allow direct comparisons for accuracy. Enumeration of missing sequence and ambiguities allowed for assessments of completeness and efficiency. All methods that used de Bruijn–based de novo assemblers were shown to produce assemblies comparable to the Sanger–sequenced plastomes but were not equally efficient. Contig assembly methods that utilized automatable and repeatable processes were generally more efficient and advantageous when applied to larger scale projects with many full plastomes. However, contig assembly methods that were less automatable and required more manual attention did show utility in determining plastomes with lower read depth that were not able to be assembled when automatable procedures were implemented. Although the methods here were used exclusively to generate grass plastomes, these could be applied to other taxonomic groups if previously sequenced plastomes were available. In addition to comparing sequencing methods, a supplemental guide for short–read plastome assembly and applicable scripts were generated for this study.